Bread and jam for Frances - Hoban, Russell. frey50; Hoban, Lillian ([New York] : HarperCollins, 1993)
Frances decides she likes to eat only bread and jam at every meal--until to her surprise--her parents grant her wish.
70924
Keywords: Badgers -- Fiction; Food habits -- Fiction